2019
DOI: 10.1159/000502377
|View full text |Cite
|
Sign up to set email alerts
|

Strong Intra-Esophageal Reflux May Contribute to the Development of Barrett’s Adenocarcinoma and Affect the Localization

Abstract: Background: There has been no study that has directly measured the esophageal reflux factors in Barrett's adenocarcinoma (BA) using 24-h multichannel intraluminal impedance-pH monitoring (24-h MII-pH). We aimed to clarify the esophageal reflux factors in Barrett's esophagus (BE) and BA and the factors that determine the location of BA with 24-h MII-pH. Methods: We performed 24-h MII-pH in 26 patients with superficial BA treated endoscopically (BA group) and 13 patients with BE (BE group) and examined the esoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
0
3
0
4
Order By: Relevance
“…It could be argued that a higher TDRE documents a more severe degree of GERD, since there is evidence that a higher TDRE correlates with increasing grades of esophagitis and Barrett’s esophagus. [ 34 , 35 ] Therefore, refractory GERD patients with evidence of an elevated number of TDRE at preoperative MII-pH monitoring may be offered LARS bust should be aware of a potential higher risk of dissatisfaction after the procedure compared to patients with normal TDRE.…”
Section: Discussionmentioning
confidence: 99%
“…It could be argued that a higher TDRE documents a more severe degree of GERD, since there is evidence that a higher TDRE correlates with increasing grades of esophagitis and Barrett’s esophagus. [ 34 , 35 ] Therefore, refractory GERD patients with evidence of an elevated number of TDRE at preoperative MII-pH monitoring may be offered LARS bust should be aware of a potential higher risk of dissatisfaction after the procedure compared to patients with normal TDRE.…”
Section: Discussionmentioning
confidence: 99%
“…A study comparing reflux metrics in patients with endoscopically treated Barrett's‐related adenocarcinoma with non‐dysplastic BE found that the total number of reflux events was greater in the adenocarcinoma group (67) compared with the BE group (45, p = 0.046). The number of acidic events (19 vs. 16) was similar, but the adenocarcinoma group had greater number of weakly acidic events (34 vs. 21, p = 0.09) and alkaline events (2 vs. 0, p = 0.042) 87 …”
Section: Esophageal Cancermentioning
confidence: 84%
“…The incidence of Barrett's adenocarcinoma (BA) has remarkably increased 3-to 6-fold in the past 20 to 40 years in Western countries and is becoming more common in Japan with time (1)(2)(3)(4)(5). BA is associated with a poor prognosis due to high rates of metastasis when detected at an advanced stage (6).…”
Section: Introductionmentioning
confidence: 99%